Reinforcing uneven development: The financialisation of Brazilian urban redevelopment projects - Mosciaro, Mayra; Pereira, Alvaro (Urban studies (Edinburgh, Scotland), 2019)
The entrepreneurial city discourse has been adopted around the globe by policymakers, with the urban redevelopment project as one of its most representative symbols. The predominantly favourable discourse revolving around this new political economy of urban space is supported by claims that newly regenerated areas bring multiple benefits to the city and its citizens. These narratives have been used in Brazil to justify increasing reliance on an urban planning tool known as Urban Operations. This planning tool, developed in the 1990s, seeks to facilitate cooperation between public and private actors in the production of new urban spaces. While projected by some as a ‘magic formula’ that enables major urban redevelopment projects without public expenditure, the outcomes of Urban Operations often differ significantly from expectations. The cases of Água Espraiada (Sa˜o Paulo) and Porto Maravilha (Rio de Janeiro) are used to demonstrate that regenerated areas, as preferred spaces for the penetration of financialised practices into the built environment, have brought forward new dynamics that are serving to reinforce pre-existing social inequalities and to exacerbate uneven development in Brazil’s main cities. 政策制定者在全球范围内采用了创业型城市论述，将城市改造项目作为其最具代表性的标志之一。支持围绕这一新的城市空间政治经济学的主要有利论述的主张是，新的再生区域为城市及其公民带来了多重利益。在巴西，这些叙述被用来证明对城市规划工具“城市运营”的越来越多的依赖的正当性。这种规划工具于20世纪90年代开发，旨在促进公共和私营部门之间在新城市空间创建方面的合作。虽然有些人认为这是一个“神奇的公式”，可以在无需公共支出的情况下完成大型城市重建项目，但城市运营的成果往往与预期大不相同。圣保罗的 Água Espraiada案例和里约热内卢的Porto Maravilha案例被用来证明，作为金融化向建筑环境渗透的首选空间，再生区域带来了新的推动力，这种推动力正在强化已存在的社会不平等，并加剧巴西大城市中的发展不平衡。